PERANAN ORANG TUA DALAM MENGATASI KENAKALAN REMAJA AKIBAT MEMINUM ALKHOHOL CAP TIKUS (Studi Kasus di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara)â€ - LOSA, JOSPIN; Tasik, Femmy; Purwanto, Antonius (Sam Ratulangi University, 2016)
Kids Teens who commit crimes were generally lacking self-control, or the control ofabusing themselves instead, and likes to enforce its own rules without regard to the presence of others in thevicinity. The incidence of such behaviour can also be caused by factors in socialization; they often hang outwith friends without looking at his background. And in general, these children very selfish, and likesto abuse or even exaggerate the price themselves. On the basis of a sense of glad they did it without regardto the effects that will be accepted. In rural areas, many acts of juvenile delinquency are very differentwith that occurs in urban areas, one of the causes of juvenile delinquency in rural areas is the drinking ofliquor among other drinks which high levels of alcohol such as the rat Stamp. Based on the backgroundof the issue that became a goal in this research is to know the role of parents in addressing the rateof juvenile delinquency as a result of the rat Stamp liquor in the village of Talawaan.The methods used in this research is qualitative research methods. In this study to understand aphenomenon in social context by nature with emphasis on the process ofdeep communication interaction between researchers with the phenomena examined. Techniquesof collection and processing of data in the research carried out in the form,namely: Observation/observation. Interview. Primary data and secondary data, the study documents.Results of the study prove that the forms of delinquency are experienced by teens affected by lackof parental control, the influence of the environment both in the school environment aswell as social environments, as well as the impact of globalization, among others, the influence of the massmedia such as television, Computer Media, and others. Results of the study prove that the forms of juveniledelinquency are extremely diverse and complex, where the offences and crimes committedby teenagers have already violated the rules and values of decency that occurred in the community suchas violating legal norms and customs.Key Words: The Role of Parents, Juvenile Delinquency, Alcohol Drinks